West to Far Michigan : Settling the Lower Peninsula, 1815-1860. - Lewis, Kenneth E. (Michigan State University Press, 2002)
West to Far Michigan is a study of the lower peninsula's occupation by agriculturalists, whose presence forever transformed the land and helped to create the modern state of Michigan. This is not simply a history of Michigan, but rather a work that focuses on why the state developed as it did. Although Michigan is seen today as an industrial state whose history is couched in terms of the fur trade and the international rivalry for the Great Lakes, agricultural settlement shaped its expansion. Using a model of agricultural colonization derived from comparative studies, Lewis exam.